2015
DOI: 10.1179/2057332415y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Effective interventions for reducing diabetes distress: systematic review and meta-analysis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 68 publications
(47 reference statements)
13
125
3
7
Order By: Relevance
“…While this is largely justified by literature demonstrating the benefits of intensive behavioral interventions [12, 80] and stronger intervention impact on glycemic control by adapting generic behavioral intervention approaches to focus on diabetes-specific constructs [81], this combination may not match the stressors or needs of all people with diabetes [82]. For example, it is possible that individuals experiencing acute or chronic general stressors might benefit more from behavioral interventions to target their unique sources of stress than a diabetes-specific intervention.…”
Section: Discussionmentioning
confidence: 99%
“…While this is largely justified by literature demonstrating the benefits of intensive behavioral interventions [12, 80] and stronger intervention impact on glycemic control by adapting generic behavioral intervention approaches to focus on diabetes-specific constructs [81], this combination may not match the stressors or needs of all people with diabetes [82]. For example, it is possible that individuals experiencing acute or chronic general stressors might benefit more from behavioral interventions to target their unique sources of stress than a diabetes-specific intervention.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these concerns, the Type 1 Diabetes Distress Scale (DDS-T1) was recently developed (27). The DDS and DDS-T1 are comprised of empirically established sub-scales such as the DDS emotional burden and regimen distress sub-scales (20,27) and have been employed in research studies (28). Short forms and screeners such as the DDS2 and PAID-5 are also available (3,(29)(30)(31)).…”
Section: Measurement Of Diabetes Distressmentioning
confidence: 99%
“…Martyn-Nemeth (2014) identified that there may be a level at which DD becomes immobilising resulting in fewer behaviours to avoid hypoglycaemia at very high levels of DD (6). Sturt et al (2015b) found that in type 1 and 2, people with elevated diabetes distress alongside psychological morbidity, including low mood, were unable to convert strongly desired self-care intentions into actions (10). Conversely, individuals with diabetes distress only were more successful at initiating self-care behaviours' and developing self-efficacy indicating that DD alone is easier to target (10).…”
Section: Self-management Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Receiving prompts as cues for action and receiving feedback on their nutritional intake alongside biofeedback through blood glucose levels are recognised behaviour change techniques that can support healthy behaviours [34]. This increased level of control over their condition and perceived treatment efficacy may additionally help reduce the levels of distress experienced [35,36].…”
Section: Opportunities For Use Of Myfood24 In a Clinical Settingmentioning
confidence: 99%